Global burden of female breast cancer: new estimates in 2022, temporal trend and future projections up to 2050 based on the latest release from GLOBOCAN - Yunmeng Zhang; Yuting Ji; Siwen Liu; Jingjing Li; Jie Wu; Qianyun Jin; Xiaomin Liu; Hongyuan Duan; Zhuowei Feng; Ya Liu; Yacong Zhang; Zhangyan Lyu; et al. (Journal of the National Cancer Center, 2025)
Background: Breast cancer (BC) incidence and mortality vary significantly across countries, highlighting the need to update the global burden of female BC, including current trends and future projections. Methods: Data were sourced from GLOBOCAN 2022, including estimated new cases and deaths from BC across 21 United Nation (UN) regions and 185 countries, the age-standardized incidence rate (ASIR) and mortality rate (ASMR), the estimated annual percentage changes (EAPC), and demographic projections through 2050. The region-specific and country-specific BC burden for women of all ages and for young women (< 40 years old) was reorganized and re-plotted to highlight subgroup differences. Linear regression was used to explore the link between ASIR/ASMR and the human development index (HDI). Transitioning countries referred to those with low or medium HDI, while transitioned countries were those with high or very high HDI. Results: In 2022, an estimated 2.3 million new BC cases and 666,000 BC-related deaths occurred globally, accounting for 23.8 % and 15.4 % of all cancer cases and deaths in women, respectively. Regionally, Eastern Asia reported the highest number of cases (480,019, ASIR: 37.54/100,000), while South-Central Asia had the highest number of deaths (135,348, ASMR: 13.41/100,000). At the country level, China had the highest number of cases due to its large population, whereas India reported the highest number of deaths. ASIR for both overall and early-onset BC increased with HDI, while ASMR for early-onset BC decreased with HDI (P < 0.05). Overall BC showed an increasing trend in ASIR during 2003–2015 (EAPC: 0.92 %) and a decreasing trend in ASMR during 2006–2016 (EAPC:-1.06 %). Early-onset BC showed a more significant rise in ASIR (EAPCs: 1.4 %) and a slight increase in ASMR (EAPCs: 0.16 %). If national rates remain stable, BC cases and deaths will increase by 54.7 % and 70.9 %, respectively, by 2050. Notably, increased early-onset BC cases are only observed in transitioning countries, while decreased cases are seen in transitioned countries. Conclusions: Breast cancer remains the leading cancer burden in women, particularly in transitioning countries. Addressing this growing burden requires urgent integration of primary prevention, early detection and high-quality treatment through multi-sectoral collaboration.